PENCIPTAAN PERTUNJUKAN VIRTUAL “JOGJA RINDUNYO DENAI” REINTERPRETASI FOLKLOR YOGYAKARTA - Nurcahyono, Wahid (TONIL: Jurnal Kajian Sastra, Teater dan Sinema, 2022)
Folklore is part of the culture of a group of people that is disseminated and passed down from generation to generation in oral form or examples accompanied by gestures of reminder aids. As residents of Yogyakarta While waiting in the village, students have the opportunity to articulate interpretations of their folkloric experiences while in Yogyakarta. The experience is articulated by accommodating the cultural elements of their local culture. This creation aims to show how folklore affects the subconscious space of the individual who gets its exposure. The results of the study are expected to be a virtual show that involves interaction between players and players and viewers in an online media. The result is expected to be a virtual performance with the theme of Yogyakarta folklore which is reinterpreted based on different local concepts. This limited online media show is a studio-scale prototype/product/artwork validation Keywords: Folklore, performances, virtual, studio.